2014
DOI: 10.17796/jcpd.38.3.w43m8474433n7ur2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Disk Position and Degenerative Bone Changes in Temporomandibular Joints of Young Subjects with TMD. An MRI Study

Abstract: This study determines the frequency and relationship between disk position and degenerative bone changes in temporomandibular joints in children and adolescent patients with internal derangement. Study design: TMJ, MRI of 88 patients were analyzed (average age: 14.7 years-old, range age: 10-18 years-old), female n=65 (73.9%) and male n=23 (26.1%). Images obtained were used to determine the frequency of disk position, joint effusion (JE) and degenerative bone changes (OA). Images were assessed by a calibrated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 47 publications
2
16
1
1
Order By: Relevance
“…However, other researchers collected both clinical exam and survey questionnaire data and found a rather impressive level of consistency between the two sets of data. 8,10,19,24,28,45 …”
Section: Discussionmentioning
confidence: 99%
“…However, other researchers collected both clinical exam and survey questionnaire data and found a rather impressive level of consistency between the two sets of data. 8,10,19,24,28,45 …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that osteoarthrosis was not observed in patients without ID, indicating a strong correlation between osteoarthrosis and ID 19 . Many studies suggested that there is a strong correlation between ADDWOR and osteoarthrosis, and specifically reported that pain increased significantly in patients with ADDWOR in concurrence with osteoarthrosis 3 20 21 22 23 . Nevertheless, such a correlation between osteoarthrosis and the possibility of pain remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 MRIs have provided essential information about disk position, morphology, and integrity. 18,[20][21][22][23][24][25][26] Cone-beam computed tomography (CBCT) has assumed a prominent role in the diagnosis of condylar remodeling. 19 Computed tomography (CT) is generally accepted as the most useful technique for assessing OA changes in the TMJs, being able to provide clinicians and researchers with detailed information on bone remodeling.…”
Section: Introductionmentioning
confidence: 99%